Mutually supportive implementation of the Plant Treaty and the Nagoya Protocol A report on ‘The International Treaty and the Nagoya Protocol : A tandem workshop for National Focal Points’, 3 - 9 June 2014, FAO, Rome, Italy - Halewood, Michael (Bioversity International, 2015)
In 2014, Bioversity International and the ABS Capacity Building Initiative led a series of interactions on the mutually supportive implementation of the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA) and the Nagoya Protocol on Access and Benefit Sharing to the Convention on Biological Diversity (CBD). These interactions included a survey among national focal points of both international agreements in 15 African countries, a four-day workshop, and a follow up analysis of inputs provided by workshop participants. This publication is the report of the four-day workshop held on 3-6 June 2014, at FAO, Rome, with 75 participants, including experts and representatives of stakeholder groups (farmers, academia, governments, regional governmental organizations), national focal points for the CBD, the Nagoya Protocol and the ITPGRFA, and members of the Secretariats of the CBD and the ITPGRFA. The core of these events were the ‘tandems’: pairs or small teams of national focal points for the Nagoya Protocol and the ITPGRFA from a single country working together. The workshop included presentations by independent experts and stakeholders whose daily activities are affected by access and benefit-sharing (ABS) regulations, and discussions on small working groups on hypothetical scenarios that evidenced overlaps and grey areas in the implementation of the ITPRGFA and the Nagoya Protocol. The ‘tandem’ approach and the work through hypothetical scenarios led to interesting reflections and proposals on the mutually supportive implementation of both international agreements. A publication that draws on the scenarios and the discussions held at the workshop was released in English, French and Spanish in 2017, Russian in 2018 and Arabic in 2019, with the title “Mutually supportive implementation of the Nagoya Protocol and the Plant Treaty: Scenarios for consideration by national focal points and other interested stakeholders”.